The EU as a global digital actor : institutionalising global data protection, trade, and cybersecurity - Fahey, Elaine (London [England] : Hart Publishing, 2022)
"This is the first book-length treatment of the advancement of EU global data flows and digital trade through the framework of European institutionalisation. Drawing on case studies of EU-US, EU-Japan and EU-China relations it charts theoretical and empirical approaches at play. It illustrates how the EU has pioneered high standards in data flows and how it engages in significant digital trade reforms, committed to those standards. The book marks a major shift in how institutionalisation and the EU should be viewed as it relates to two of the more extraordinary areas of global governance: trade and data flows. This significant book will be of interest to EU constitutional lawyers, as well as those researching in the field of IT and data law."--
Introduction -- 1. EU as a Global Data Actor: Nudging Convergence and Capture -- 2. EU as a Digital Trade Actor -- 3. EU as a Cyber Actor: Institutionalising EU Cyber Law -- 4. On the Transatlantic Divide: Beyond Weak Institutionalisation -- 5. East Asia Convergence: EU-Japan Relations and Data -- 6. East Asian Reverse Convergence? EU-China Relations
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Data protection -- Law and legislation -- European Union countries; Computer security -- Law and legislation -- European Union countries; European Union countries -- Foreign economic relations -- 21 century; Electronic books